Coupled quintessence with a [lambda]CDM background: removing the [sigma]8 tension - Barros, Bruno J.; Amendola, Luca; Nunes, Nelson (Arxiv, 2018)
A well-known problem of the $Λ$CDM model is the tension between the relatively high level of clustering, as quantified by the parameter $σ_8$, found in cosmic microwave background experiments and the smaller one obtained from large-scale observations in the late Universe. In this paper we show that coupled quintessence, i.e. a single dark energy scalar field conformally coupled to dark matter through a constant coupling, can solve this problem if the background is taken to be identical to the $Λ$CDM one. We show that two competing effects arise. On one hand, the additional scalar force is attractive, and is therefore expected to increase the clustering. On the other, in order to obtain the same background as $Λ$CDM, coupled quintessence must have a smaller amount of dark matter near the present epoch. We show that the second effect is dominating today and leads to an overall slower growth. Comparing to redshift distortion data, we find that coupled quintessence with $Λ$CDM background solves the tension between early and late clustering. We find for the coupling $β$ and for $σ_8$ the best fit values $β = ± 0.079^{+0.016}_{-0.019}$ and $σ_8 = 0.818^{+0.028}_{-0.028}$. These values also fit the lensing data from the KiDS-450 survey. We also estimate that the future missions SKA and Euclid will constrain $β$ with an error of $±\, 7.2×10^{-4}$ and for $σ_8$ of $± \,8.0×10^{-4}$ at $1σ$ level.